Presentation – Practice – Production (PPP) Method: An Alternative Method Used in Enhancing student’s Vocabulary Mastery - Hamdani, Zohri; Amrizal, Amrizal (ETERNAL (English Teaching Journal), 2018)
The purposes of the study were to describe application of PPP method in teaching vocabulary at University of Muhammadiyah Lampung, especially General lesson in Islamic Education and to know the result of students’ vocabularies achievement after teaching by using PPP method. The population of study was University of Muhammadiyah Lampung, especially General lesson in Islamic Education. And there were thirty students as sample. The data of collecting method used documentation and test. The analysis data used mean of average. The students’ mastery of vocabularies has improved after PPP method was given. It was supported by the significant different result of the standard score that has been taken from the English teacher, mean was lower 59.5 than the last score in action research, mean was 72.5. The following suggestions are offered. First, the use of a PPP Method should be maintained frequently and recommended to the English teacher, especially to teach children around 7-10 in order to attract their motivation in learning English to be more interested. Second, a teacher should be clever in creating a contusive situation; try to apply other teaching strategies so that the class becomes alive. Hopefully, there would be further studies on teaching English using PPP Method.